Los proyectos de inclusión social del gad parroquial de la esperanza y su incidencia en el empoderamiento de las personas vulnerables, año 2023 - Sanchez Zambrano, Brittany Delia (2025)
This research was conducted in the Parish GAD of La Esperanza, located in the province of Los Ríos, canton of Quevedo, parish of La Esperanza. The objective of the study was to evaluate the impact of social inclusion projects implemented by the Parish GAD of La Esperanza on the empowerment of vulnerable people. It was an exploratory, analytical, and descriptive study. The methodology used included an interview with the president of the GAD and a survey of 50 participants in the various social programs. The analysis of the results reveals a mostly positive assessment by the beneficiaries of the social inclusion projects implemented by the Parish GAD of La Esperanza. The participants reported having received clear information about the actions carried out, which encouraged their active participation and understanding of the purpose of the initiatives. Significant effects were identified in strengthening self- esteem, personal confidence, and the development of decision-making skills. The training and motivational activities contributed to individual empowerment and greater integration into the community. The institutional support provided by the GAD was considered adequate, and the importance of maintaining effective coordination with the MIES to ensure the continuity and effectiveness of the programs was recognized. The findings show that inter-institutional coordination is a key factor in consolidating sustainable processes that positively impact the lives of people in vulnerable situations.